A cross-cultural study of ostensible invitations in English and Indonesian: Linguistic and pragmatic perspectives - Hendar, Hendar; Simatupang, Ervina C.M.; Zuraida, Ida (Universitas Ahmad Dahlan, 2025)
This study investigates ostensible invitations in English and Indonesian from a cross-cultural perspective, focusing on their linguistic forms and pragmatic functions. Ostensible invitations—offers made without a genuine expectation of acceptance—are examined through naturally occurring conversations, role-play data, and discourse analysis. The study draws on politeness theory, speech act theory, and high- vs. low-context cultural frameworks to explore how indirectness, formulaic expressions, and contextual cues convey non-literal intent. In English, ostensible invitations often employ vague or non-committal phrasing to minimize imposition and protect negative face, such as “We should get together sometime.” In Indonesian, they frequently appear in culturally prescribed forms like Main ke rumah kapan-kapan (“Come to my house sometime”), functioning to maintain social harmony (kerukunan) and express positive politeness. Findings reveal that while both languages use ostensible invitations to manage interpersonal relationships, their underlying motivations and interpretive cues differ due to contrasting cultural values, such as individualism in English-speaking contexts and collectivism in Indonesian society. The research highlights implications for intercultural communication, language teaching, and translation, aiming to reduce misunderstandings caused by differing pragmatic norms.